Decision-Making Process for Tourism Potential Segmentation - Fandi Achmad; Irsyad Thalib Abdillah; Husni Amani (International Journal of Innovation in Enterprise System, 2023)
The tourism industry is one of the critical sectors driving regional economic development, creating jobs, and preserving cultural and natural heritage. The Rembang Regency Government is trying to design a strategy to increase various tourism potentials that support the tourism industry. Stakeholders cannot optimally manage various tourism potentials in Rembang Regency because the support system facilities still need to be improved. Potential tourism segmentation based on facility support systems (SSF) can assist the government in carrying out strategies to increase the potential of the tourism industry. The main objective of this research is to assist stakeholders in the decision-making process and generate policy advice through tourist mapping results, reducing large-scale tourism industry problems to a scale that can be understood and acted upon in successful tourism industry marketing. Methods in data collection using literature study and observation with accidental sampling to determine as many as 20 tours. The K-Means method was chosen to classify tourism potential in Rembang Regency, Central Java, Indonesia. The results showed three potential tourism clusters in Rembang Regency based on Support System and Facilities (SSF) covering telecommunication, power source, transportation, waste management, location, clean water source, supporting industry, spatial, hospitality, safety, and security. The results of this study can be used in designing decision-making strategies by stakeholders to improve the tourism industry. Increasing the potential of each tourist cluster by stakeholders has its advantages and disadvantages.